PENGEMBANGAN MODUL UNTUK PEMBELAJARAN BIOLOGI BERKARAKTER DI SMA NEGERI 1 SUNGAI LIMAU KABUPATEN PADANG PARIAMAN - Hayati, Rina; Haviz, M.; Delfita, Rina (Jurnal Pembelajaran MIPA, 2014)
The purpose of this research is get a module for learning biology based on character that valid and practice. The kind of this research that used is research of development. The model of developmental that used in this research areÂ 4-D, they are define, design, develop and disseminate. Procedure of research have been done is there phase, they are define phase, design phase and develop phase. Based on the result of this research module for learning biology based on character is very valid andÂ practice. Therefore the quality of product development was conducted valid and practical based on the result validate and practicality have been done.Key words: development, module, biology, character